Impact of Latent Tuberculosis Infection on Neurocognitive Functioning and Inflammation in HIV-Infected and Uninfected South Indians. (1st August 2020) - LaVergne, Stephanie; Umlauf, Anya; McCutchan, Allen; Heaton, Robert; Benson, Constance; Kumarasamy, Nagalingeswaran; Bharti, Ajay R.
Abstract : Background: HIV-associated neurocognitive disorder persists in some people living with HIV despite optimal antiretroviral therapy. Latent tuberculosis infection (LTBI) may cause systemic inflammation and immune activation that may impair brain function. We assessed cognition and biomarkers of inflammation in both HIV+ and HIV− South Indians with and without LTBI. Methods: Adults (≥18 years old) with and without HIV infection were screened for LTBI by interferon-gamma release assays, completed comprehensive neurocognitive assessments, and underwent measurement of serum inflammatory biomarker levels. Results: The participants (n = 119) were HIV+/LTBI+ (n = 15), HIV+/LTBI− (n = 50), HIV−/LTBI+ (n = 26), and HIV−/LTBI− (n = 28). HIV+ participants, regardless of LTBI status, had more impaired global deficit scores than HIV− participants (odds ratio = 3.42, P = 0.028, adjusted for sex and education differences). Neither global deficit scores nor impairment rates differed in the LTBI+ group compared with the LTBI− group ( P = 0.79 and P = 0.41, respectively). The mean log10 interleukin (IL)-6 and monocyte chemoattractant protein-1 values were significantly higher and high sensitivity C-reactive protein lower in the LTBI+ group than the LTBI− group ( P = 0.044, 0.023, and 0.03, respectively, adjusting for HIV status and sex). Conclusions: In this cross-sectional study of South Indians, HIV infection, but not LTBI, was associated with increased neurocognitive impairment. Proinflammatory biomarkers (IL-6 and monocyte chemoattractant protein-1, but not tumor necrosis factor-α) were elevated in the LTBI+ groups compared with the LTBI− groups. Biomarkers of immune activation (interferon-γ, macrophage inflammatory protein-1β, IL-2, interferon gamma inducible protein-10, RANTES, and IL-22) did not differ between these groups. Larger longitudinal studies should be conducted to confirm our findings that the effect of LTBI on systemic inflammation or neurocognitive impairment is likely small.